The incidence of atrial fibrillation with trastuzumab treatment: A systematic review and meta‐analysis. Issue 6 (28th November 2018) - Yuan, Ming; Tse, Gary; Zhang, Zhiwei; Han, Xu; Wu, William K. K.; Li, Guangping; Xia, Yunlong; Liu, Tong
Summary: Aim: Cases of cardiotoxicity related to trastuzumab have been reported. This systematic review and meta‐analysis evaluated the risk of atrial fibrillation (AF) in patients of breast cancer treated with trastuzumab. Methods: PubMed and EMBASE were searched until September 2017 for articles that investigated AF incidence in patients receiving trastuzumab for breast cancer. Results: A total of 15 studies involving 8124 patients treated with trastuzumab were included. Of the total cohort, 37 patients suffered from AF, giving rise to an incidence of 1.22% (95% confidence interval [CI]: 0.56%‐2.68%). No significant difference in the incidence of AF was found between ado‐trastuzumab emtansine (0.95%, 95% CI: 0.36%‐2.52%) and trastuzumab groups (1.32%, 95% CI: 0.52%‐3.34%), trastuzumab combined with other antineoplastic agents (2.09%, 95% CI: 1.16%‐3.73%) and trastuzumab alone (0.36%, 95% CI: 0.04%‐3.08%), prior exposure to anthracyclines (1.72%, 95% CI: 0.75%‐3.88%) and no prior exposure (1.03%, 95% CI: 0.30%‐3.51%), and radiotherapy (1.26%, 95% CI: 0.68%‐2.33%) vs. no radiotherapy (1.21%, 95% CI: 0.35%‐4.14%). Conclusions: Atrial fibrillation incidence in breast cancer patients receiving trastuzumab was around 1.2%. It was not influenced by the formulation of trastuzumab, the additional use of neoplastic agents, anthracycline exposure status, or concurrent radiotherapy.